"MY RESISTING GETTING WELL": NEURASTHENIA AND SUBCONSCIOUS CONFLICT IN PATIENT‐PSYCHIATRIST INTERACTIONS IN PREWAR AMERICA. Issue 2 (24th February 2016) - LAMB, SUSAN
Abstract : This study examines experiences of individual patients and psychiatrists in the Henry Phipps Psychiatric Clinic at Johns Hopkins between 1913 and 1917. The dynamics of these patient‐psychiatrist interactions elucidate the well‐known conceptual shift in explanations of mental illness during the twentieth century, from somatic models rooted in the logic of "neurasthenia" and damaged nerves to psychodynamic models based on the notion of "subconscious conflict." A qualitative analysis of 336 cases categorized as functional disorders (a catchall term in this period for illnesses that could not be confirmed as organic diseases), shows that patients explained their symptoms and suffering in terms of bodily malfunctions, and, particularly, as a "breakdown" of their nervous apparatus. Psychiatrists at the Phipps Clinic, on the other hand, working under the direction of its prominent director, Adolf Meyer, did not focus their examinations and therapies on the body's nervous system, as patients expected. They theorized that the characteristic symptoms of functional disorders—chronic exhaustion, indigestion, headaches and pain, as well as strange obsessive and compulsive behaviors—resulted from a distinct pathological mechanism: a subconscious conflict between powerful primal and social impulses. Phipps patients were often perplexed when told their physical symptoms were byproducts of an inner psychological struggle; some rejected the notion, while others integrated it with older explanations to reconceptualize their experiences of illness. The new concept also had the potential to alter psychiatrists' perceptions of disorders commonly diagnosed as hysteria, neurasthenia, or psychoneuroses. The Phipps records contain examples of Meyer and his staff transcending the frustration experienced by many doctors who had observed troubling but common behaviors in such cases: morbid introspection, hypochondria, emotionalism, pity‐seeking, or malingering. Subconscious conflict recast these behaviors as products of "self‐deception, " which both absolved the sufferer and established an objective clinical marker by which a trained specialist could recognize functional disorder. Using individual case studies to elucidate the disjunction between patients' and psychiatrists' perspectives on what all agreed were debilitating illnesses, this analysis helps to illuminate the origins of a radical transformation in psychiatric knowledge and popular culture in the twentieth century—from somatic to psychodynamic explanations of mental illness.